Metacognition and mobile-assisted vocabulary learning - Mohd. Asraf, Ratnawati; Supian, Nadya (Arab World English Journal, 2017)
Mobile Assisted Language Learning, known as MALL, is an approach to language learning that is enhanced through the use of a mobile device, such as mobile phones. The ubiquitousness of mobile phones has opened up more platforms for vocabulary learning, resulting in increased metacognition among learners; which can be seen as a predictor of successful vocabulary learning.This article describes the results of a study conducted on 21 undergraduates that analysed the most frequently used activities facilitating self-directed mobile-assisted vocabulary learning outside the classroom based on the pedagogical framework for mobile assisted language teaching and learning. The study also looked into to the extent these activities enhanced the learners’ metacognition. Data was collected from video reports, interviews and an activity log, and analysed according to the pedagogical framework for mobile assisted language teaching (Kukulska-Hulme, Norris, & Donohue, 2015). The findings revealed that the most frequent activities utilized outside the classroom were (1) using online dictionaries to assist with understanding word meanings, (2) using video features on their phones for speaking and pronunciation practice of new words and (3) posting on social media as a means of practicing their newly acquired vocabulary in writing. The self-directed nature of these activities were reported by the participants as enhancing their metacognitive skills, resulting in increased learner confidence and deeper gains in vocabulary learning. The implications of these findings are discussed.